Aspirin and other nonsteroidal anti‐inflammatory drugs, statins and risk of non‐Hodgkin lymphoma. Issue 3 (8th March 2021) - Liebow, Mark; Larson, Melissa C.; Thompson, Carrie A.; Nowakowski, Grzegorz S.; Call, Timothy G.; Macon, William R.; Kay, Neil E.; Habermann, Thomas M.; Slager, Susan L.; Cerhan, James R.
Abstract: Non‐steroidal anti‐inflammatory drugs (NSAIDs) and statin drugs may protect against the development of non‐Hodgkin lymphoma (NHL), but data are limited, particularly for NHL subtypes. Furthermore, some in vitro, animal and epidemiologic data suggest there may be a synergistic effect of these two agents, but there has been no test of this hypothesis in NHL. We evaluated the self‐reported use of NSAIDs and statins in a clinic‐based study of 1703 NHL patients and 2199 frequency‐matched controls. Unconditional logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs), adjusted for potential confounding variables. We observed an inverse association of regular use of low‐dose aspirin with risk of NHL (OR = 0.82; 95% CI 0.70‐0.96) that was stronger with longer duration of use ( P  < .01). There were no associations for use of regular or extra‐strength aspirin, ibuprofen, other NSAIDs, statins or other cholesterol‐lowering drugs with NHL risk, while an inverse association with COX‐2 inhibitors was equivocal. There was also no interaction of low‐dose aspirin and statins on NHL risk. Inverse associations of similar magnitude to all NHL were observed for regular use of low‐dose aspirin with diffuse large B‐cell, follicular, marginal zone and all other lymphomas, although not all associations were statistically significant. In conclusion, low‐dose aspirin but not regular/extra strength aspirin, other NSAIDs or statin use was associated with lower risk of NHL. Beyond the potential for the primary prevention of NHL, these data also point to a role of anti‐platelet or other effects of low‐dose aspirin in lymphomagenesis that warrant follow‐up. Abstract : What's new? Non‐steroidal anti‐inflammatory drugs (NSAIDs) and statin drugs may protect against the development of non‐Hodgkin lymphoma, but data are limited, particularly for subtypes of the disease. In this large case‐control study, regular use of low‐dose aspirin was inversely associated with risk of non‐Hodgkin lymphoma and most non‐Hodgkin lymphoma subtypes. There was no association with use of regular/extra‐strength aspirin, ibuprofen, other NSAIDs, or cholesterol‐lowering drugs. Beyond the potential of low‐dose aspirin in the primary prevention of non‐Hodgkin lymphoma, these data point to a role of anti‐platelet or other effects of low‐dose aspirin in lymphomagenesis that warrants follow‐up.